RESOLUTION 48 FROM 07.07.2009 "ON APPROVAL OF SANR&N (SANITARY REGULATIONS AND NORMS) 2.1.3.2524-09 "SANITARY AND HYGIENIC REQUIREMENTS TO THE DENTAL MEDICAL ORGANIZATIONS. AMENDMENT 2 TO THE SANR&N 2.1.3.1375-03" - . Роспотребнадзор (Радиационная гигиена)
.